Age/autoimmunity-associated B cells in inflammatory arthritis: An emerging therapeutic target - Li, Zhen-yu; Cai, Ming-Long; Qin, Yi; Chen, Zhu (Frontiers in Immunology, 2023)
Age/autoimmunity-associated B cells (ABCs) are a novel B cell subpopulation with a unique transcriptional signature and cell surface phenotype. They are not sensitive to BCR but rely on TLR7 or TLR9 in the context of T cell-derived cytokines for the differentiation. It has been established that aberrant expansion of ABCs are linked to the pathogenesis of systemic autoimmune diseases such as systemic lupus erythematosus. Recently, we and other groups have shown that increased ABCs are associated with rheumatoid arthritis (RA) disease activity and have demonstrated their pathogenic role in RA, indicating that targeting specific B cell subsets are a promising strategy for the treatment of inflammatory arthritis. In this review, we summarize the current knowledge of ABCs, focusing on their emerging role in the pathogenesis of inflammatory arthritis. A deep understanding of the biology of ABCs in the context of inflammatory settings in vivo will ultimately contribute to the development of novel targeted therapies for the treatment of inflammatory arthritis.